On sufficient conditions for the technical stability of controlled processes with lumped parameters - Matviichuk, K. S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
On the basis of the theory of differential inequalities and Lagrange multipliers, we develop a method for the investigation of conditions for the technical stability of continuously controlled processes with lumped parameters.